Factors That Contribute to Differences in Survival of Black vs White Patients With Colorectal Cancer - Sineshaw, Helmneh M. (Gastroenterology, 2017)
BACKGROUND & AIMS: Previous studies reported that black vs white disparities in survival among elderly patients with colorectal cancer (CRC) were due to differences in tumor characteristics (tumor stage, grade, nodal status, and comorbidity) rather than differences in treatment. We sought to determine the sequential contribution of differences in insurance, comorbidity, tumor characteristics, and treatment receipt to the black-white survival disparity among patients with CRC in 18–64 years old. METHODS: We used data from the National Cancer Database, a hospital-based cancer registry database sponsored by the American College of Surgeons and the American Cancer Society, on non-Hispanic black (black) and non-Hispanic white (white) patients, 18–64 years old, diagnosed from 2004 through 2012 with single or first primary invasive stage I–IV CRC. Blacks were sequentially matched by demographics, insurance, comorbidity, tumor characteristics, and treatment with 5 white partially overlapping subgroups using propensity score and greedy matching algorithm. We used the Kaplan-Meier method to estimate 5-year survival, and Cox proportional hazards models to generate hazard ratios (HR). RESULTS: The absolute 5-year survival difference between black and white unmatched patients with CRC was 9.2% (57.3% for black patients vs 66.5% for white patients; P < .0001). The absolute difference in survival did not change after patient groups were matched for demographics, but decreased to 4.9% (47% relative decrease [4.3% of 9.2%]) when they were matched for insurance and to 2.3% when they were matched for tumor characteristics (26% relative decrease [2.4% of 9.2%]). Further matching by treatment did not reduce the difference in 5-year survival between black and white patients. In proportional hazards model, insurance and tumor characteristics matching accounted for the 54% and 27% excess risk of death in black patients, respectively. CONCLUSIONS: In an analysis of data from the National Cancer Database, we found that insurance coverage differences accounted for approximately one-half of the disparity in survival rate between black vs white patients with CRC in 18–64 years old; tumor characteristics accounted for a quarter of the disparity. Affordable health insurance coverage for all populations could substantially reduce differences in survival times of black vs white patients with CRC.